Pengaruh Literasi Terhadap Tingkat Berpikir Kritis Siswa Kelas V di SD 064973 Bhayangkara Medan - Asisi Febrina Simatupang; Ananda Tampubolon; Ancelina Simbolon; Arinda Gloria Saragih; Dwi Tarisya; Grace Manullang; Immanuel Hasiholan Siregar; Isyrofirrahmah Br. Nasution; Raiga Yesica Br. Manalu; Ribka Trifena Putri Gea; Wulandari Wulandari (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to examine the effect of a literacy programs the critical thinking skills of fifth grade students at SDN 064873 Bhayangkara, Percut Sei Tuan District. The research method used is a qualitative approach with a pre-experimental design using a one-group pretest-posttest design. A total of 20 fifth grade students were the subjects of this research. Data was collected through a pretest and posttest consisting of 20 multiple choice questions. The research results showed that after being given treatment in the form of a literacy program by reading non-learning story books for 15 minutes before learning, there was a significant increase in students critical thinking abilities. The average posttest score (84) has increased significantly compared to the average pretest score (54), with a difference of 30. These results indicate that literacy programs can contribute positively to improving students critical thinking abilities. Therefore, there is a need to emphasize the development of literacy programs in the educational context to improve the quality of education and produce students who have better critical thinking skills.